Formulation and Drug Release Study of Rivaroxaban Oral Disintegrating Tablets Using Various Super-Disintegrants - Siddheshwar, Suhas Shivaji; Ghorpade, Asmita Bhausaheb; Mankar, Someshwar Dattatraya; Dighe, Santosh Bhausaheb (International Journal of Experimental Research and Review, 2023)
This study aims to improve Rivaroxaban's solubility, dissolution, and bioavailability. Orally disintegrating tablets (ODTs) made with super-disintegrants like crospovidone, sodium starch glycolate, and cross-carmellose sodium will do this. Tablet preparation used direct compression and formulation optimization with design expert software. After a thorough factorial design and evaluation of pre- and post-compression parameters, the F3 batch, which contained Rivaroxaban (7.97%), Crospovidone (3.59%), Croscarmellose sodium (5.18%), Sodium Starch Glycolate (5.18%), Lactose Anhydrous (31.08%), Mannitol (15.94%), MCC (27.89%), SSF (1.59%), and Talc (1.59%), was the best. The enhanced tablet formulation (F3) showed positive qualities, including 3.3 kg/cm² hardness, 23 seconds disintegration time, and 99% drug release after 30 minutes. The innovative Rivaroxaban orally disintegrating tablet (ODT) method disintegrated and dissolved faster than market forms. Rivaroxaban's physical and chemical properties were assessed before formulation. The medication was colorless, scentless, crystalline, and melted at 227°C-229°C, as described in published research. The pharmaceutical was found to be a BCS Class II drug with low water solubility and high solubility in acetate buffer pH 4.5 and 0.1 N Hydrochloric acid. Fourier-transform infrared spectroscopy (FTIR) confirmed no drug-polymer-excipient interactions. Every batch of tablets exhibited uniform thickness (3.5 mm to 3.8 mm) and diameter (10.31 mm to 10.36 mm), indicating good compression without adhering to shaping tools. All samples had a 3-5 kg cm-² hardness, indicating strong mechanical properties. The Roche friability method showed that all batches had good abrasion resistance, ranging from 0.1% to 0.5%. Variations in croscarmellose sodium and crospovidone on tablet disintegration time and hardness were examined using design expert software. The ANOVA showed important factors affecting these attributes. Data-driven polynomial equations predict tablet disintegration time and hardness. These models reveal formulation parameters that affect tablet performance. Thus, the improved F3 batch of rivaroxaban orally disintegrating tablets (ODTs) improves solubility, dissolving, and bioavailability. This may improve treatment outcomes.